2016
DOI: 10.2139/ssrn.2837755
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Good Trader? On the Role of Intuition and Reflection on Trader Performance

Abstract: Using simulations and experiments, we pinpoint two main drivers of trader performance: cognitive reflection and theory of mind. Both dimensions facilitate traders' learning about asset valuation. Cognitive reflection helps traders use market signals to update their beliefs whereas theory of mind offers traders crucial hints on the quality of those signals. We show these skills to be complementary because traders benefit from understanding the quality of market signals only if they are capable of processing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…The Chat-no reputation treatment also showed, in line with our model, that people who earned a high score on a validated honesty scale (see Ashton, Lee and de Vries, 2014) were more inclined to release informative messages in the communication platform. This was the case even after controlling for standard measures of prosociality (see and cognitive skills (see Noussair, Tucker and Xu, 2014;Hefti, Heinke and Schneider, 2016;Corgnet, DeSantis and Porter, 2018). Importantly, chat improved the informational efficiency of markets even in the absence of reputational concerns because price deviations from the true asset value were significantly lower in the Chat-no reputation treatment compared to No Chat.…”
Section: Overview Of Our Studymentioning
confidence: 94%
See 3 more Smart Citations
“…The Chat-no reputation treatment also showed, in line with our model, that people who earned a high score on a validated honesty scale (see Ashton, Lee and de Vries, 2014) were more inclined to release informative messages in the communication platform. This was the case even after controlling for standard measures of prosociality (see and cognitive skills (see Noussair, Tucker and Xu, 2014;Hefti, Heinke and Schneider, 2016;Corgnet, DeSantis and Porter, 2018). Importantly, chat improved the informational efficiency of markets even in the absence of reputational concerns because price deviations from the true asset value were significantly lower in the Chat-no reputation treatment compared to No Chat.…”
Section: Overview Of Our Studymentioning
confidence: 94%
“…We elicited participants' cognitive reflection and theory of mind skills (see ) using the Cognitive Reflection Test, (CRT, henceforth) and the eye gaze test (TOM, henceforth). These skills have been identified as predictors of traders' earnings in experimental markets (see Noussair, Tucker and Xu, 2014;Hefti, Heinke and Schneider, 2016;Bossaerts, Suzuki and O'Doherty, 2018;Corgnet, DeSantis and Porter, 2018).…”
Section: End-of-experiments Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…Bond traders are also likely to be more strategically sophisticated than undergraduate students exposed to bond trading for the first time. For example, Thoma et al (2015) reports that professional traders have higher score in Cognitive Reflection Test (CRT, Frederick, 2005) which is positively correlated with the profits subjects make in various asset market experiments (see, among others, Breaban and Noussair, 2015;Corgnet et al, 2015Corgnet et al, , 2018 than bankers, non-financial professionals, or average students. Furthermore, Breaban and Noussair (2015) and Bosch-Rosa et al (2018) show a negative correlation between the magnitude of mis-pricing observed in the experimental asset market and the average degree of sophistication (measured, for example, by the average CRT scores) of market participants.…”
Section: Insights and Conclusionmentioning
confidence: 99%